Venous cerebral thrombosis. Mechanical and chemical thrombolysis. - Fernandes, António (2003)
Cerebral Venous Thrombosis is a disease not fully understood regarding its pathophysiology, natural course and prognosis. The therapeutics is not consensual. However it has been normally used anticoagulants plus thrombolysis or anticoagulation alone. The authors report the successful lysis of dural sinus thrombosis by mechanical and chemical (rt-PA) treatment.